Synthesis of Therapeutic Oligonucleotides (Springer Singapore, 2018)
This book presents the latest knowledge on a broad range of topics relating to the synthesis of natural and artificial oligonucleotides with therapeutic potential. Nucleic acid-based therapeutics are attracting much attention, and numerous therapeutic oligonucleotides, such as antisense oligonucleotides, siRNAs, splice-switching oligonucleotides, and nucleic acid aptamers, are being evaluated in clinical trials for the treatment of a variety of diseases. Synthesis of Therapeutic Oligonucleotides covers a broad range of topics in the field that are of high relevance to researchers, including the synthesis of natural and chemically modified oligonucleotides, the development of novel nucleic acid analogs, industrial scale synthesis and purification of oligonucleotides, and important aspects of chemistry, manufacturing, and controls (CMC). The aim is to provide new insights and inspire fresh ideas in nucleic acid chemistry that may ultimately lead to novel concepts and techniques and the discovery of more effective nucleic acid drugs. The book will be of high value for both established researchers in the field and students intending to specialize in nucleic acid chemistry research.